Improved VSS-LMS based Control for Autonomous AC Microgrid for Rural Areas - Samoon, Farhat Afzah; Hussain, Ikhlaq; Iqbal, Sheikh Javed (2023 IEEE 3rd International Conference on Sustainable Energy and Future Electric Transportation (SEFET), 2023)
In this paper, renewable energy-based autonomous AC microgrid comprising of a photovoltaic system (PV), a diesel generator set (DEGS) and the battery energy storage is connected through a bidirectional converter (BDC) is presented. For maximum power extraction from the PV system incremental conductance (INC) algorithm is used. Battery energy storage is used to maintain power balance in the proposed microgrid. BDC control prevents the battery from second harmonics, so increasing life of the battery. Power quality improvement is achieved by controlling VSC using Improved variable step size least mean square (VSS-LMS) adaptive algorithm. Comparative analysis in terms of convergence, oscillations and total harmonic distortion is presented. I-VSS-LMS provides better performance than other conventional adaline-based VSC controls. The performance of system is studied under various steady state and dynamic conditions. System performs satisfactorily as per IEEE 519 standards. MATLAB/ simpower tools is used for the simulation of the RE-based microgrid system.